2011
DOI: 10.1183/09031936.00061811
|View full text |Cite
|
Sign up to set email alerts
|

Anti-reflux surgery in lung transplant recipients: outcomes and effects on quality of life

Abstract: Fundoplication may improve survival after lung transplantation. Little is known about the effects of fundoplication on quality of life in these patients. The aim of this study was to assess the safety of fundoplication in lung transplant recipients and its effects on quality of life.Between June 1, 2008 and December 31, 2010, a prospective study of lung transplant recipients undergoing fundoplication was undertaken. Quality of life was assessed before and after surgery. Body mass index (BMI) and pulmonary func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 32 publications
2
30
1
Order By: Relevance
“…Resolution of reflux symptoms as well as significant improvement in satisfaction with their condition was observed after antireflux procedures. These data support other authors findings [19,20]: Burton in 2009 found that after laparoscopic Toupet fundoplication in lung transplant patients 88% of the patients rated the surgery as excellent, Robertson et al noticed significant improvement in reflux symptoms index and gastrointestinal quality of life scores. However most of the studies evaluate short-term fundoplication effect.…”
Section: Discussionsupporting
confidence: 85%
“…Resolution of reflux symptoms as well as significant improvement in satisfaction with their condition was observed after antireflux procedures. These data support other authors findings [19,20]: Burton in 2009 found that after laparoscopic Toupet fundoplication in lung transplant patients 88% of the patients rated the surgery as excellent, Robertson et al noticed significant improvement in reflux symptoms index and gastrointestinal quality of life scores. However most of the studies evaluate short-term fundoplication effect.…”
Section: Discussionsupporting
confidence: 85%
“…46,47,49 Studies have reported a decreased rate of lung function decline aft er laparoscopic fundoplication in lung allograft recipients who had GERD. 50,51 Further exploration is needed to assess the eff ects of GERD and aspiration on the clinical course and outcome of lung allograft recipients.…”
Section: Bronchiolitis Obliterans Syndromementioning
confidence: 99%
“…These conditions promote gastro-oesophageal reflux, which increases the risk of aspiration in lung transplant recipients who also have impaired cough ability and impaired mucociliary clearance. Reflux and aspiration probably contribute to chronic lung dysfunction [4,26,29,30], and anti-reflux surgery has been proposed in order to improve lung graft function [5,31,32]. In lung transplant and heart-lung transplant recipients there is an association between reflux and respiratory infections [33].…”
Section: Discussionmentioning
confidence: 99%
“…Contact of the graft with the environment, inadequate lymphatic drainage and the effects of nerve damage during transplantation on airway clearance all increase the risk of lung infection. Post-operative gastroparesis can delay gastric emptying and thereby increase the risk of gastro-oesophageal reflux, aspiration and respiratory infection [4,5]. In addition, ventilator-associated tracheobronchitis (VAT) and ventilator-associated pneumonia (VAP) may complicate the post-operative course and may have severe consequences in this highly immunosuppressed population.…”
Section: Introductionmentioning
confidence: 99%